The Effect of Nigella Sativa L. Extract on Blood Glucose Levels in Alloxan-Induced Hyperglycemic Mus musculus - Khoirunnisa, Nur; Makmun, Armanto; Surdam, Zulfiyah; Nur, Muhammad Jabal; Ardiansar, Abdul Mubdi; Zulfahmidah, Zulfahmidah (Newinera Publisher, 2025)
Hyperglycemia is one of the conditions of increasing blood glucose levels. There are various treatment options in patients with hyperglycemia, one of which is non-drug therapy with traditional medicine. A traditional medicinal plant with various benefits, namely black cumin which is known to have a variety of ingredients that can lower blood glucose levels. Knowing the effect of black cumin extract on blood glucose levels in mice with alloxane-induced hyperglycemia. The research design used was a pre and post test with control group design with a total sample of 27 mice divided into 3 groups where each group consisted of 9 heads. Group 1 is the control group while group 2 and group 3 will be treated respectively. The analysis was carried out with a paired sample t-test to see the differences between each group before and after treatment. The results of the study on the average blood glucose levels before treatment and after the administration of black cumin treatment there were changes in each group obtained a significance value of 0.000 at both doses of black cumin extract. Based on the results obtained, it is known that black cumin extract can reduce blood glucose levels where the greater the dose is directly proportional to the decrease in blood glucose levels.